URARIA PICTA (JACQ.): A REVIEW ON ETHNOMEDICAL USES, PHYTOCHEMISTRY, AND BIOLOGICAL ACTIVITIES: Uraria Picta (Jacq.): A Review - MANE, JAYKUMAR; NAGORE, DHEERAJ; CHITLANGE, SOHAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The aim of this systematic review is to provide an in-depth study of ethnological uses, phyto-chemistry, pharmacological activities, and toxicological research in Uraria picta (Jacq.), to identify remaining gaps, and to provide a basis for future research. By searching for the words “U. picta” and “Prishnaparni” in electronic databases such as SciFinder, Web of Science, PubMed, and Google Scholar, information on common uses, phytochemistry, and pharmacological activities was systematically collected. Phytochemical analysis of U. picta shows various components such as alkaloids, flavonoids, steroids, terpenoids, phenols, and saponins. The extracts and their isolated components showed numerous in vitro and in vivo pharmacological effects, including urinary tract diseases, tumors, edema, smoking, and dyspnea. On the other hand, searches of patent databases found almost seven applications, highlighting the differences between a large number of published scientific articles and non-existent patent applications. This event demonstrates the technological potential of undiscovered species. Ethnographic research shows that U. picta, an important Asian medicinal plant, is used to treat many diseases. In this review, the ethnobotanical, phytochemical, pharmacological, and ethnological properties of various morphological parts of the U. picta plant are highlighted. Future research has provided information for commercial research and has shown that this herb has tremendous potential for pharmaceutical and nutritional applications.